Kualitas Pelayanan Publik Bidang Administrasi Kependudukan di Kecamatan Telanaipura Kota Jambi - Dedek Kusnadi (Universitas Katolik Widya Karya Malang, 2023)
The government as a provider of public services needed by the community must be responsible and continue to strive to provide the best service for the sake of improving public services. On the other hand, community satisfaction is a measure of the success of public services provided by public service providers. This research is a descriptive study using a qualitative approach to determine the quality of public services in the field of population administration in Telanaipura District, Jambi City. The data analysis technique used is an interactive model. The results showed that the quality of public services in the field of population administration in Telanaipura District, Jambi City, was seen from the aspects of physical facilities, reliability, responsiveness, assurance, empathy, that is, the Public Services section in Telanaipura District, Jambi City had not fulfilled adequate service facilities to provide services to the community. The community is satisfied with the services provided by Telanaipura District, Jambi City in the reliability aspect regarding reliability in handling any community complaints. Employees in terms of helping people who need services, especially people who are confused about services, have been seen between officers and visitors who communicate with each other. Security in Telanaipura District, Jambi City, has shown efforts to improve the quality of its services in relation to providing a sense of security for the community. The empathy given by the Telanaipura District, Jambi City, is to give a pleasant impression.